Social protection and livelihoods : marginalised migrant workers of India and Bangladesh - Abrar, Chowdhury Rafiqul; Seeley, Janet (Dhaka : University Press, 2009)
Contributed articles.
Includes bibliographical references (pages [209]-220) and index.
GenEd
Keywords: Migrant labor -- Bangladesh; Migrant labor -- India; Economics; Migration, Internal -- Social aspects -- Bangladesh; Migration, Internal -- Social aspects -- India; Migration, Internal -- Economic aspects -- Bangladesh; Migration, Internal -- Economic aspects -- India